The Influence of Leadership Styles on Employee Motivation and Organizational Performance in the Service Sector - Budi Santoso; Agus Hidayat; Tuti Andriani (International Journal of Economics, Management and Accounting, 2024)
This study investigates how different leadership styles, such as transformational and transactional, affect employee motivation and organizational performance within the service sector. Through a survey of service-based organizations, the research highlights the relationship between leadership approach, employee satisfaction, and overall productivity. Findings suggest that transformational leadership significantly enhances motivation and performance, offering a strategic advantage in a competitive market.